Historians and the Film, Filmmakers and History. Where Two Disciplines Meet and Overlap - Ferenčuhová, Mária (Iluminace, 2004)
The study examines the relationship of historians to fiction and documentary films and the relationship of filmmakers to history.
Keywords: film historians; historical research; historical events in film; historical events and film; historical figures in film